Pilot evaluation of a Psychological First Aid online training for COVID-19 frontline workers in American Indian/Alaska Native communities - O'Keefe, Victoria M.; Grubin, Fiona; Vaidya, Nainika; Maudrie, Tara L.; Conrad, Maisie; Neuner, Sophie; Jridi, Shardai; Cook, Mary Ann; Carson, Kathryn A.; Barlow, Allison; Haroz, Emily E. (Frontiers in Public Health, 2024)
Introduction The COVID-19 pandemic exacerbated mental health concerns and stress among American Indians and Alaska Natives (AI/ANs) in the United States, as well as among frontline workers responding to the pandemic. Psychological First Aid (PFA) is a promising intervention to support mental wellbeing and coping skills during and after traumatic events, such as the COVID-19 pandemic. Since PFA is often implemented rapidly in the wake of a disaster or traumatic event, evidence evaluating its impact is lacking. This paper reports pilot evaluation results from a culturally adapted PFA training designed to support COVID-19 frontline workers and the AI/AN communities they serve during the pandemic. Methods This study was designed and implemented in partnership with a collaborative work group of public health experts and frontline workers in AI/AN communities. We conducted a pre-post, online pilot evaluation of a culturally adapted online PFA training with COVID-19 frontline workers serving AI/AN communities. Participants completed a baseline survey and two follow-up surveys 1 week and 3 months after completing the PFA training. Surveys included demographic questions and measures of anxiety, burnout, stress, positive mental health, communal mastery, coping skills, PFA knowledge, confidence in PFA skills, and satisfaction with the PFA training. Results Participants included N = 56 COVID-19 frontline workers in AI/AN communities, 75% were AI/AN, 87% were female, and most (82%) were between the ages of 30–59. Participants reported high satisfaction with the training and knowledge of PFA skills. Pilot results showed significant increases in positive mental health and social wellbeing and reductions in burnout from baseline to 3 months after completing the PFA training among frontline workers. There were no changes in communal mastery, coping skills, stress, or anxiety symptoms during the study period. Discussion To our knowledge, this is the first pilot evaluation of a PFA training designed and culturally adapted with and for AI/AN communities. Given that many AI/AN communities were disproportionately impacted by COVID-19 and prior mental health inequities, addressing acute and chronic stress is of crucial importance. Addressing traumatic stress through culturally adapted interventions, including Indigenous PFA, is crucial to advancing holistic wellbeing for AI/AN communities.